Pemanfaatan Tabel 3X3 untuk Meningkatkan Pemahaman Konsep Pemfaktoran Kuadrat - Agus Prianto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The use of Table 3X3 is one way that mathematics teachers can make it easy for students to understand the quadratic factoring concept. The aim of this research is to describe the learning process using Table 3X3 which can improve the understanding of the quadratic factoring concept of class VIII G students of SMP Negeri 1 Jepara. This research is a classroom action research which is carried out in two cycles. Each cycle consists of four components, namely: planning, action, observation, and reflection. The results showed that the use of Table 3X3 can improve understanding of the quadratic factoring concept as indicated by an average test score of 16.39 or 24.38% in end cycle, from an average score of 67.29 in the first cycle to 83, 68 in the second cycle and the achievement value of 75 is from 58.33% in the first cycle to 72.22% in the second cycle. Thus it can be concluded that the use of Table 3X3 can improve the understanding of the quadratic factoring concept.